The Potential of Polish Bioeconomy Compared to the European Union Countries - Anna Nowak; Aneta Jarosz-Angowska; Artur Krukowski (Przegląd Prawno-Ekonomiczny)
Bioeconomy has become one of the major directions in the development of the European Union (EU). This is a response to global challenges including sustainable management of natural resources, sustainable production, public health improvement, mitigation of adverse effects of climate change, and integrated social and economic development. This article aimed to describe how bioeconomy develops and how significant it is to the European Union and evaluate the potential of bioeconomy in Poland in comparison to other EU member states. The potential of bioeconomy was analysed according to the level and structure of employment, gross value added generated by this sector of the economy, as well as according to labour productivity. The analysis was based on an official classification of economic activity in Europe (NACE). The timeline of the study was 2008 and 2017, which allowed evaluating changes that occurred over a decade. The analysis involved data deriving from the European Commission’s statistical database. The studies imply that in 2017 Poland ranked first in the EU in terms of the number of bioeconomy workers, whereas differences in the structure of employment could be observed between Poland and the whole EU. They mostly referred to a higher share of employment in Polish agriculture, with a lower percentage of employment in the food, beverage and tobacco sector. In addition, Poland had a 5% share in generating the Gross Value Added (GVA) of the EU bioeconomy, which put it fifth among all the member states. The GVA of bioeconomy in Poland had a structure similar to that presented by the whole EU with Food, beverage and tobacco and Agriculture being the most significant sectors and Bio-based electricity and Liquid biofuels being relatively insignificant. In addition, in all the sectors labour productivity was lower than on average in the EU.